Perlakuan Perpajakan Terhadap Non Performing Loan ( NPL) Dalam Perspektif Hukum Pajak - Budi Ispriyarso (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
Non Performing Loan ( NPL ) is a default loans, includes doubtful loans, non-performing loans and bad credits. The emerging of NPLs that not immediately solved may lead to unhealthy situation for the concerned bank. According to the tax law studies, the dispute of NPLs due to the differences opinion whether it could be included as a deduction from gross income or not being used to calculate the taxable income. Such differences come off due to legal uncertainty of the the regulations governing the NPLs. Hence, it is necessary that the regulation of NPLs should reflect the fairness and legal certainty. Key Word : Non Performing Loan, Tax Dispute